Association of ECG parameters with late gadolinium enhancement and outcome in patients with clinical suspicion of acute or subacute myocarditis referred for CMR imaging. - Kady Fischer; Maximilian Marggraf; Anselm W Stark; Kyoichi Kaneko; Ayaz Aghayev; Dominik P Guensch; Adrian T Huber; Michael Steigner; Ron Blankstein; Tobias Reichlin; Stephan Windecker; Raymond Y Kwong; et al. (PLoS ONE)
Background Risk stratification of myocarditis is challenging due to variable clinical presentations. Cardiovascular magnetic resonance (CMR) is the primary non-invasive imaging modality to investigate myocarditis while electrocardiograms (ECG) are routinely included in the clinical work-up. The association of ECG parameters with CMR tissue characterisation and their prognostic value were investigated in patients with clinically suspected myocarditis. Methods and results Consecutive patients with suspected myocarditis who underwent CMR and ECG were analysed. Major adverse cardiovascular event (MACE) included all-cause death, hospitalisation for heart failure, heart transplantation, documented sustained ventricular arrhythmia, or recurrent myocarditis. A total of 587 patients were followed for a median of 3.9 years. A wide QRS-T angle, low voltage and fragmented QRS were significantly associated with late gadolinium enhancement. Further, a wide QRS-T angle, low voltage and prolonged QTc duration were associated with MACE in the univariable analysis. In a multivariable model, late gadolinium enhancement (HR: 1.90, 95%CI: 1.17-3.10; p = 0.010) and the ECG parameters of a low QRS voltage (HR: 1.86, 95%CI: 1.01-3.42; p = 0.046) and QRS-T-angle (HR: 1.01, 95%CI: 1.00-1.01; p = 0.029) remained independently associated with outcome. The cumulative incidence of MACE was incrementally higher when findings of both CMR and ECG were abnormal (p<0.001). Conclusion In patients with clinically suspected myocarditis, abnormal ECG parameters are associated with abnormal tissue characteristics detected by CMR. Further, ECG and CMR findings have independent prognostic implications for morbidity and mortality. Integrating both exams into clinical decision-making may play a role in risk stratification in this heterogeneous patient population.